2015
DOI: 10.7314/apjcp.2015.16.5.2061
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Human Colon Cancer Cells in Nude Mice is Delayed by Ketogenic Diet With or Without Omega-3 Fatty Acids and Medium-chain Triglycerides

Abstract: Background: Tumors are largely unable to metabolize ketone bodies for energy due to various deficiencies in one or both of the key mitochondrial enzymes, which may provide a rationale for therapeutic strategies that inhibit tumor growth by administration of a ketogenic diet with average protein but low in carbohydrates and high in fat. Materials and Methods: Thirty-six male BALB/C nude mice were injected subcutaneously with tumor cells of the colon cancer cell line HCT116. The animals were then randomly split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 38 publications
(36 reference statements)
1
55
0
Order By: Relevance
“…The KD and similar diets used as a monotherapy have a pluripotent effect on the growth on tumors both in vitro and in vivo which may depend, at least in part, on the model system, the specific metabolic intervention and the molecular underpinnings of the tumor itself (Freedland et al, 2008; Otto et al, 2008; Mavropoulos et al, 2009; Stafford et al, 2010; Kim H. S. et al, 2012; Caso et al, 2013; Poff et al, 2013, 2015; Simone et al, 2013; Lv et al, 2014; Shukla et al, 2014; Hao et al, 2015; Woolf et al, 2015). In addition, the exact composition of the diet may also alter its effects, and there are studies in some cancers looking specifically at polyunsaturated fatty acids (PUFAs), particularly the omega-3 class, for their anti-cancer properties (Sauer et al, 2007; Pifferi et al, 2008; Wang et al, 2012, 2016; Hofmanova et al, 2013; Abel et al, 2014).…”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The KD and similar diets used as a monotherapy have a pluripotent effect on the growth on tumors both in vitro and in vivo which may depend, at least in part, on the model system, the specific metabolic intervention and the molecular underpinnings of the tumor itself (Freedland et al, 2008; Otto et al, 2008; Mavropoulos et al, 2009; Stafford et al, 2010; Kim H. S. et al, 2012; Caso et al, 2013; Poff et al, 2013, 2015; Simone et al, 2013; Lv et al, 2014; Shukla et al, 2014; Hao et al, 2015; Woolf et al, 2015). In addition, the exact composition of the diet may also alter its effects, and there are studies in some cancers looking specifically at polyunsaturated fatty acids (PUFAs), particularly the omega-3 class, for their anti-cancer properties (Sauer et al, 2007; Pifferi et al, 2008; Wang et al, 2012, 2016; Hofmanova et al, 2013; Abel et al, 2014).…”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
“…The striking feature of the work done to date in a number of model systems using different dietary interventions is that alterations in metabolism have a far reaching effect on tumor cells, tumors and the tumor microenvironment. Studies have shown reductions in growth rate as one might expect however, there are also changes in the formation of reactive oxygen species and oxidative stress (Stafford et al, 2010; Milder and Patel, 2012; Allen et al, 2013), angiogeneisis (Zhou et al, 2007; Jiang and Wang, 2013; Woolf et al, 2015), hypoxia (Maurer et al, 2011; Poff et al, 2015; Woolf et al, 2015), inflammation and peri-tumoral edema (Mavropoulos et al, 2009; Woolf et al, 2015), metastasis and invasion (Gluschnaider et al, 2014; Lv et al, 2014; Hao et al, 2015; Poff et al, 2015) and the expression of various transcriptional and post-transcriptional modulators such as NF-κB (Woolf et al, 2015) and microRNAs (Pazmandi et al, 2015). …”
Section: The Ketogenic Diet: Overview and Preclinical Evidencementioning
confidence: 99%
“…[22] split animals into three feeding groups: A KD rich in omega 3 fatty acids and medium-chain triglycerides (MCT) (MKD group), lard only (LKD group) and SD group for 45 days. All animals in KD groups intake the UR-KD and showed a clear increase in body weight in duration of study.…”
Section: Resultsmentioning
confidence: 99%
“…Body weights remained similar in intervention and control groups despite the major differences in the caloric and composition content of mentioned diets. [101215161819202225]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation